Transparency and accountability of accounts: requirements of the social responsibility of non-agricultural cooperatives in Cuba - Bencomo Fariñas, Yaneisi; Fernández Pacheco, Daimi (REVESCO. Revista de Estudios Cooperativos, 2019)
The link between cooperative principles and the values that cooperativism promotes, and the commitment inherent in the concept of Social Responsibility, justify the need for cooperatives to articulate mechanisms in their management processes to channel all their efforts in favor of greater Social Responsibility. To such ends, these subjects must have a model of social management implies the conclusion of transparent accountability practices that promote social justice, equity and local development through the consequent compliance with the principles and values of the cooperativist philosophy. In this way, policies, strategic plans, concrete initiatives, communication channels will be necessary, in short, a formal structure that supports this management process, equipped with mechanisms for evaluation and control; actions all aimed at responding to the expectations of its stakeholders, as well as improving the transparency and legitimacy of cooperatives. The aim of this paper is to analyze, from a critical standpoint, the main legal and practical limitations regarding compliance with and control of the Cooperative Social Responsibility of Non-Agricultural Cooperatives in Cuba. In view of its fulfillment, in the first place, doctrinal positions on the relationship between transparency and Social Responsibility are systematized, given the link between the inspiring principles of the cooperative culture and the Cooperative Social Responsibility, and of the latter with the disclosure levels of information. It concludes with reflections on the role played by the Cooperative Social Balance as an instrument of accountability that demands and demands a more transparent cooperative management in the development of the social mission that, together with the deployment of its economic activity, must be fulfilled by the Cuban cooperatives.